2012
DOI: 10.1111/j.1462-5822.2012.01799.x
|View full text |Cite
|
Sign up to set email alerts
|

ESX‐1‐mediated translocation to the cytosol controls virulence of mycobacteria

Abstract: SummaryMycobacterium species, including Mycobacterium tuberculosis and Mycobacterium leprae, are among the most potent human bacterial pathogens. The discovery of cytosolic mycobacteria challenged the paradigm that these pathogens exclusively localize within the phagosome of host cells. As yet the biological relevance of mycobacterial translocation to the cytosol remained unclear. In this current study we used electron microscopy techniques to establish a clear link between translocation and mycobacterial viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
393
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(408 citation statements)
references
References 59 publications
10
393
0
5
Order By: Relevance
“…Bacterial levels at 24‐hr postinfection (hpi) were analysed with FACS and compared with uptake of these bacteria by RAW macrophages. RAW macrophages phagocytosed both strains with similar efficiency, both at 2 and 24 hpi (Figure 7a), confirming previous reports that the level of phagocytosis of M. marinum WT and our esx‐1 mutant are similar (Houben et al, 2012; Simeone et al, 2012; van der Wel et al, 2007). …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Bacterial levels at 24‐hr postinfection (hpi) were analysed with FACS and compared with uptake of these bacteria by RAW macrophages. RAW macrophages phagocytosed both strains with similar efficiency, both at 2 and 24 hpi (Figure 7a), confirming previous reports that the level of phagocytosis of M. marinum WT and our esx‐1 mutant are similar (Houben et al, 2012; Simeone et al, 2012; van der Wel et al, 2007). …”
Section: Resultssupporting
confidence: 89%
“…ESX‐1 secretion mutants are severely attenuated (Davis & Ramakrishnan, 2009; Stoop et al, 2011; Volkman et al, 2004), but most importantly for our purposes, these mutants are unable to complete the macrophage infection cycle and are therefore predominantly located inside phagocytic cells (Houben et al, 2012; Simeone et al, 2012; van der Wel et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies using electron microscopy (EM) and a fluorescence resonance energy transfer‐based method showed that Mtb also localizes in the cytosol in THP‐1 macrophages, primary human macrophages and primary human DCs (van der Wel et al ., 2007; Houben et al ., 2012; Simeone et al ., 2012). The ESX‐1 type VII secretion system (T7SS) that is lacking from most of the non‐pathogenic mycobacterial strains (Abdallah et al ., 2007) is required for Mtb localization in the cytosol.…”
Section: Cell Autonomous Defence Mechanisms In Tbmentioning
confidence: 99%
“…After uptake by immune phagocytes, the bacteria arrest phagosomal maturation and convert their vacuole into a replication-permissive compartment. Both bacteria can translocate into the host cell cytosol dependent on an intact Region-of-Difference-1-locus (RD1) (8)(9)(10)(11). The genomic RD1-locus encodes a secretion system, ESX-1 (Type-VII secretion system), which has been associated with mycobacterial virulence (ref.…”
mentioning
confidence: 99%